No association between wolframin gene H611R polymorphism and mood disorders: Evidence from 2570 subjects. (February 2015) - Tang, Xiao-Wu; Wang, Juan; Zou, Yan-Feng
Abstract Background: In the past few decades, a number of studies have investigated the association of the wolframin (WFS1) gene H611R polymorphism with mood disorders, but the findings are not always consistent. Aims: The objective of the present study is to assess the association between WFS1 gene H611R polymorphism and mood disorders by using a meta-analysis. Methods: A comprehensive literature search of PubMed, Excerpta Medica Database, Elsevier Science Direct and China National Knowledge Infrastructure databases was conducted to identify relevant articles, with the last report up to April 15, 2014. Pooled odds ratio (OR) with 95% confidence interval (CI) was estimated. Results: Seven studies including 1318 cases and 1252 controls were selected from potentially relevant articles. This meta-analysis showed that there was no significant association between WFS1 gene H611R polymorphism and mood disorders (R vs. H: OR = 0.93, 95% CI = 0.82–1.05, P = 0.22; HR+ RR vs. HH: OR = 0.98, 95% CI = 0.82–1.17, P = 0.80; RR vs. HH+ HR: OR = 0.84, 95% CI = 0.67–1.04, P = 0.11; RR vs. HH: OR = 0.86, 95% CI = 0.67–1.10, P = 0.24; HR vs. HH: OR = 1.03, 95% CI = 0.78–1.36, P = 0.83). In subgroup analyses by ethnicity, we did not detect any significant association of this polymorphism with mood disorders in Caucasian and Asian populations (P > 0.05). In subgroup analyses by types of mood disorders, we also did not detect any significant association of this polymorphism with bipolar disorder or major depressive disorder (P > 0.05). Conclusions: The results of this meta-analysis suggest that there is no association between WFS1 gene H611R polymorphism and mood disorders.